Environmental fate and ecotoxicological effects of antiretrovirals: A current global status and future perspectives. (15th November 2018) - Ncube, Somandla; Madikizela, Lawrence M.; Chimuka, Luke; Nindi, Mathew M.
Abstract: The therapeutic efficacy of antiretroviral drugs as well as challenges and side effects against the human immunodeficiency virus is well documented and reviewed. Evidence is available in literature indication that antiretrovirals are only partially transformed and become completely excreted from the human body in their original form and/or as metabolites in urine and feces. The possibility of massive release of antiretrovirals through human excreta that enters surface water through surface runoff and wastewater treatment plant effluents is now of environmental concern because the public might be experiencing chronic exposure to antiretrovirals. The primary concern of this review is limited data concerning environmental fate and ecotoxicity of antiretrovirals and their metabolites. The review aims to provide a comprehensive insight into the evaluation of antiretrovirals in environmental samples. The objective is therefore to assess the extent of analysis of antiretrovirals in environmental samples and also look at strategies including instrumentation and predictive models that have been reported in literature on the fate and ecotoxicological effects due to presence of antiretrovirals in different environmental compartments. The review also looks at current challenges and offers possible areas of exploration that could help minimize the presence of antiretrovirals in the environment. Graphical abstract: Image Highlights: Over 20 tons of ARVs are consumed every day. ARVs have been found in environmental samples and this is of public health concern. SPE using Oasis HLB followed by LC-MS determination is the main analysis approach. Higher concentrations of ARVs are in African water bodies and WWTP effluents. More datasets needed for better understanding of fate and ecotoxicity of ARVs.